Fatigue life prediction of dentin-adhesive interface using micromechanical stress analysis - Singh, Viraj; Park, Jonggu; Spencer, Paulette; Ye, Qiang; Kieweg, Sarah L.; Marangos, Orestes; Misra, Anil S. (My University, 2011)
Objectives: The objective of this work was to develop a methodology for the prediction of fatigue life of the dentin-adhesive (d-a) interface. Methods: At the micro-scale, the d-a interface is composed of dissimilar material components. Under global loading, these components experience different local stress amplitudes. The overall fatigue life of the d-a interface is, therefore, determined by the material component that has the shortest fatigue life under local stresses. Multiple 3d finite element (FE) models were developed to determine the stress distribution within the d-a interface by considering variations in micro-scale geometry, material composition and boundary conditions. The results from these models were analyzed to obtain the local stress concentrations within each d-a interface component. By combining the local stress concentrations and experimentally determined stress versus number of cycle to failure (S-N) curves for the different material components, the overall fatigue life of the d-a interface was predicted. Results: The fatigue life was found to be a function of the applied loading amplitude, boundary conditions, microstructure and the mechanical properties of the material components of the d-a interface. In addition, it was found that the overall fatigue life of the d-a interface is not determined by the weakest material component. In many cases, the overall fatigue life was determined by the adhesive although exposed collagen was the weakest material component. Comparison of the predicted results with experimental data from the literature showed both qualitative and quantitative agreement. Significance: The methodology developed for fatigue life prediction can provide insight into the mechanisms that control degradation of the bond formed at the d-a interface. © 2011 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Adhesive; Bond; Dentin; Fatigue; Finite element; Hybrid layer; Interface